2017
DOI: 10.1093/ntr/ntx036
|View full text |Cite
|
Sign up to set email alerts
|

Anhedonia and Abstinence as Predictors of the Subjective Pleasantness of Positive, Negative, and Smoking-Related Pictures

Abstract: Taken together, these findings provide tentative evidence that anhedonia is associated with a relative imbalance in the motivational salience of drug relative to nondrug rewards and may be associated with a generalized hypo-reactivity to both positive and negative stimuli. Though some prior smoking research has evidenced this relative imbalance in anhedonia with self-report or a smoking-choice task, we additionally show that this pattern may extend to hyper-affective reactivity to smoking-related stimuli being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…This suggests that the altered ratings of pleasant and unpleasant images was accounted for by the OAT group's elevated anhedonia, and that effects on ratings of drug images may have also been partially accounted for by anhedonia. This is consistent with a previous study in people with nicotine dependence, which found that this combined pattern (blunting of subjective response to both pleasant and unpleasant images and increased ratings of drug stimuli) was related to anhedonia 19 . However this contrasts with Gerra et al 's 10 finding that abstinent participants with heroin dependence rated unpleasant images as more unpleasant than controls.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This suggests that the altered ratings of pleasant and unpleasant images was accounted for by the OAT group's elevated anhedonia, and that effects on ratings of drug images may have also been partially accounted for by anhedonia. This is consistent with a previous study in people with nicotine dependence, which found that this combined pattern (blunting of subjective response to both pleasant and unpleasant images and increased ratings of drug stimuli) was related to anhedonia 19 . However this contrasts with Gerra et al 's 10 finding that abstinent participants with heroin dependence rated unpleasant images as more unpleasant than controls.…”
Section: Discussionsupporting
confidence: 93%
“…However, previous studies that reported associations between OUD and P3 responses during pleasant images did not report matching participants according to tobacco use. In light of reports of altered responses to pleasant stimuli in tobacco smokers 19,20 , this may be a critical difference in the present study, and points to the importance of considering the role of nicotine when examining altered responses to affective stimuli in substance use disorder populations.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Few studies ( n = 4) used behavioral tasks. Guillot et al used the Picture Rating Task, which is a measure of affective valence related to positive, negative, and smoking cues (27). In this task, participants were instructed to rate the pleasantness of each stimulus by pressing keys corresponding to seven-point Likert scale from −3 (very unpleasant) to 3 (very pleasant).…”
Section: Resultsmentioning
confidence: 99%
“…In summary, the Cook study was by far the most rigorous study and it found a significant effect of abstinence that was related to inability to stop smoking. This, plus the several other positive results 29 Self-selected reward ratings (none) Cook et al 41 Ratings of rewards (20%) Ratings of lab stimuli Guillot et al 44 Ratings of positive pictures (none) Anhedonia scales Hughes et al 40 AES (6%) REI enjoyment (5%) TEPS (none) TEPS (6%) Lawn et al 27 Ratings of rewards (none) SHAPS (150%) Powell et al 43 SHAPS (71%) 28 Music (18%) Money (none) Perkins et al 42 Music (49%) Perkins et al 37 Music (22%) Video (31%) Money (none) Perkins et al 38 Music (21%) Video (25%) Rewards' influence on responding Kalamboka et al 45 Experiment 1 Money (none) Powell 43 Money (15%) Choosing more frequent/larger rewards Audrain-McGovern et al 29 Money (none) Hughes et al 40 Money (none) Money (none) Pergadia et al 30 Money (98%)…”
Section: Self-reportsmentioning
confidence: 92%